Multifunctional Sandwich‐Structured Electrolyte for High‐Performance Lithium–Sulfur Batteries. Issue 3 (2nd January 2018) - Qu, Hongtao; Zhang, Jianjun; Du, Aobing; Chen, Bingbing; Chai, Jingchao; Xue, Nan; Wang, Longlong; Qiao, Lixin; Wang, Chen; Zang, Xiao; Yang, Jinfeng; Wang, Xiaogang; et al.
Abstract: Due to its high theoretical energy density (2600 Wh kg −1 ), low cost, and environmental benignity, the lithium–sulfur (Li‐S) battery is attracting strong interest among the various electrochemical energy storage systems. However, its practical application is seriously hampered by the so‐called shuttle effect of the highly soluble polysulfides. Herein, a novel design of multifunctional sandwich‐structured polymer electrolyte (polymer/cellulose nonwoven/nanocarbon) for high‐performance Li‐S batteries is demonstrated. It is verified that Li‐S battery with this sandwich‐structured polymer electrolyte delivers excellent cycling stability (only 0.039% capacity decay cycle −1 on average exceeding 1500 cycles at 0.5 C) and rate capability (with a reversible capacity of 594 mA h g −1 at 4 C). These electrochemical performances are attributed to the synergistic effect of each layer in this unique sandwich‐structured polymer electrolyte including steady lithium stripping/plating, strong polysulfide absorption ability, and increased redox reaction sites. More importantly, even with high sulfur loading of 4.9 mg cm −2, Li‐S battery with this sandwich‐structured polymer electrolyte can deliver high initial areal capacity of 5.1 mA h cm −2 . This demonstrated strategy here may open up a new era of designing hierarchical structured polymer electrolytes for high‐performance Li‐S batteries. Abstract : A novel design of multifunctional sandwich‐structured polymer electrolyte is demonstrated for high performance lithium‐sulfur batteries. The assembled lithium‐sulfur battery delivers superior cycling stability and rate capability. The performance is attributed to the synergistic effect of each layer in the polymer electrolyte. This strategy may open up a new era of designing hierarchical structured polymer electrolytes for high‐performance lithium‐sulfur batteries.